logo sm

zurückQA 2013, Teil  B - Lösungen: Nr. III/1

Löse folgende Gleichung:

-4,9 x + 0,5*(6x + 4) - 4*(0,85 - 1,1x) = (-11,25 x + 40)*0,2 + 19,1

Lösung

-4,9 x + 0,5*(6x + 4) - 4*(0,85 - 1,1x) = (-11,25 x + 40)*0,2 + 19,1
-4,9 x +     3 x + 2   -    3,4 + 4,4 x   =      - 2,25 x + 8      + 19,1
              2,5 x        -          1,4         =     - 2,25 x        +      27,1    | + 1,4
            4,75 x                                 =                               28,5     | : 4,75
                   x                                 =                                 6

Angaben ohne Gewähr

Zum Seitenanfang